Multiple species of grayling ( Thymallus sp.) found in sympatry in a remote tributary of the Amur River - Steven Weiss; Giulia Secci‐Petretto; Alexander Antonov; Elsa Froufe (Zoologica Scripta, 2020)
Large‐scale phenotypic and genetic studies of the salmonid genus Thymallus (grayling) in the Palaearctic suggest that most major phylogeographic lineages represent good biological species. Evaluating such a premise in areas involved in palaeo‐hydrological dynamics where multiple species are found in sympatry should serve to assess the level of reproductive isolation, the traditional sine qua non of species recognition. Molecular sequence (mtDNA) and microsatellite (nDNA, seven loci) analysis of grayling in the upper Bureya River watershed support the occurrence of three distinctive species of grayling living in sympatry in this large oligotrophic tributary of the Amur River. One of these lineages is primarily found throughout the Lena River basin and is recognized as Baikal‐Lena grayling Thymallus baicalolenensis ; the second, the upper Amur grayling Thymallus grubii is found over large areas of the Amur catchment including the entire headwater region; and the third, the Bureya grayling Thymallus burejensis is endemic to the study area. A limited number of hybrids were identified, primarily between Baikal‐Lena grayling T. baicalolenensis and Bureya grayling T. burejensis with little to no signs of introgression among non‐hybrid individuals. Morphological distinctiveness among populations of these species living in sympatry was greater than between populations living in allopatry, suggesting character displacement. Divergence estimates among taxa range up to 6.2 MY, and allopatric origins for all three species’ is suggested. To our knowledge, this is the first data‐based confirmation of three species of grayling living in sympatry.